MANAJEMEN PEMBELAJARAN DI MADRASAH ALIYAH NEGERI (MAN) 3 PALEMBANG - Dewi Rayuni (Ta'dib: Jurnal Pendidikan Islam, 2010)
This research try to comprehend implementation of learning management at Madrasah Aliyah Negeri (MAN) 3 Palembang, South Sumatera. It finds that learning procedure has been implemented by teachers of MAN 3 Palembang. It includes: planning, actuating, organizing, and supervising/evaluating in a relatively good manner. But in the aspect of evaluation, there is still a weakness, i.e.: teachers feel little difficulty in doing daily learning evaluation for each of class. In increasing teacher competency in learning management, they follow some of seminars, trainings, surfing the internet, discussing with peer teacher, etc. Madrasah’s headmaster also support in improving teacher competency by enrolling the teachers in seminars, trainings, completing learning media and learning resources, and held meeting in every end of semester.